(3GdJdaRjhf h GdeLJeY (B:s (3GdNUGFU(B, (3GdJCKjQ$1 (3GdfhYjI(B, (3GdEYdGfGJ (B/s - (3chQfR, Lhfs; (3COjHs ((3OeTb (B:s (3COjH NVhQ ,s, 1999)
(3jbOe GdcJGH KbGaI GYdGejI LOjI JZfj GdfXQjI h GdeeGQSI h JfajP OQGSj h eeGQSj GdGYdGe GdYQH h gPG eG JgOa Gdjg SdSdI GdecJHI GdGYdGejI h gPG eG OaYfG Gdi JQLeI GdcJGH h fTQgs
Keywords: (3GdeLJeYs; (3Yde GdGLJeGY s; (3GdJdaRjhfs